Inflammation and Aortic Stiffness: An Individual Participant Data Meta‐Analysis in Patients With Inflammatory Bowel Disease. Issue 10 (10th October 2017) - Zanoli, Luca; Boutouyrie, Pierre; Fatuzzo, Pasquale; Granata, Antonio; Lentini, Paolo; Oztürk, Kadir; Cappello, Maria; Theocharidou, Eleni; Tuttolomondo, Antonino; Pinto, Antonio; Cammà, Calogero; Licata, Anna; et al.
Abstract : Background: The recent finding that aortic pulse wave velocity (aPWV) is increased in patients with inflammatory bowel disease may explain why the cardiovascular risk is increased despite the low prevalence of traditional cardiovascular risk factors. We aimed to test whether inflammation is associated with aortic stiffening in this setting after adjustment for major confounders and to perform subgroup analyses. Methods and Results: A systematic literature search for aPWV in inflammatory bowel disease was performed using PubMed, Scopus, Web of Science, and Google Scholar databases (last accessed May 7, 2017). Inclusion criterion was peer‐reviewed publications on clinical studies reporting original data. This study followed the Preferred Reporting Items for Systematic Review and Meta‐Analyses of individual participant data 2015 guidelines. Data were provided for 4 cohorts in 3 countries (151 participants with ulcerative colitis, 159 with Crohn's disease, and 227 control patients). Using aPWV, cohort‐specific z scores were calculated after loge ‐transform and combined in meta‐analysis to form pooled effects using a random‐effects model. Compared with controls, aPWV was increased in patients with Crohn's disease (mean difference 0.78 z score; 95% confidence interval, 0.56–1.00 z score [ P <0.001]) and ulcerative colitis (mean difference 0.75 z score; 95% confidence interval, 0.52–0.97 z score [ P <0.001]). In an outlier‐robust multivariate linear regression model adjusted for prespecified confounders, aPWV was associated with disease duration (years, β=0.05 z score; 95% confidence interval, 0.02–0.08 z score [ P <0.001]) and white blood cell count (billion cells/L, β=0.07 z score; 95% confidence interval, 0.02–0.11 z score [ P =0.002]) but not with markers of acute inflammation (C‐reactive protein and erythrocyte sedimentation rate), cardiovascular risk factors, and therapy. Conclusions: The increased aPWV reported in patients with inflammatory bowel disease is associated with inflammation. Clinical Trial Registration: URL:http://www.crd.york.ac.uk . Unique identifier: PROSPERO 2016: CRD42016053070.